Pengaruh Tasawuf Akhlaki terhadap Prilaku Sosial Mahasiswa Program Studi Aqidah dan Filsafat Islam Angkatan 2019 Fakultas Ushuluddin dan Studi Islam UINSU Medan - Nasution, Novita; Andy, Safria; Damanik, Agusman (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The topic was brought up by the researcher as a student's encounter with moral Sufism, which is defined by social behavior. Some pupils behave badly in social situations. Students today tend to undervalue moral ideals, which leads them to believe that social interaction in the classroom and in society is unimportant. They also prefer to disregard their responsibilities, which they should fulfill. The purpose of this study is to ascertain how Moral Sufism affects the social behavior of students enrolled in the 2019 class of the Islamic Aqidah and Philosophy Study Program at the Faculty of Ushuluddin and Islamic Studies, University of the Nija. The author's primary data source for this study was informants, who were gathered using a qualitative approach method. Specifically, students enrolled in the 2019 Aqidah and Islamic philosophy study program. The data gathering method used in this study is based on references from multiple Sufism moral texts, as well as on the findings of interviews and field observations. According to the study's findings, moral sufism encourages students to act in a way that is socially responsible for people around them by attempting to achieve equilibrium in the forms of social conduct that are already prevalent, such as in the classroom, family, and community. Moral Sufism's moral principles serve as a form of control and discipline, ensuring that students' higher education experiences remain unblemished by external influences.